Ethnobotanical Uses of Some Common Plants in Uttarakhand, India: A Review - Chhaya Singh; Priyanka Nautiyal; Neha Chauhan; Shagun Gupta (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
Due to varying climate and topography there s a wide range of vegetation which serve as habitats to diverse species of wild life. Due to the richness in variety of vegetation the forest occupies a place of pride in the environment. The present study focuses on the Ethnobotanical uses of some common plants of Matli village, Uttarkashi district. 15 tree species belonging to 14 families common in the area have been reported. All the plants reported from the area have medicinal importance. The details of the plants such as botanical name, family, parts used, uses, common name, plant parts most harvested and the use of different parts for different medicinal purpose etc are also given in the paper. Future conservation efforts should pay particular attention to the value of medicinal plants and incorporate measures to ensure their preservation and long-term viability. Additional research is needed to fully understand several features of these plants, including their photochemical, biochemical, antibacterial, antifungal, and antihelminthic properties.